Experimental investigation of the shear strength of one‐way reinforced concrete (RC) slabs subjected to concentrated loads and in‐plane transverse axial tension. (16th September 2021) - Fernández, Pablo G.; Marí, Antonio; Oller, Eva
Abstract: This paper presents the results of an experimental campaign carried out to investigate the effects of in‐plane transverse tensile forces on the shear strength of linearly supported one‐way reinforced concrete (RC) slabs without shear reinforcement subjected to concentrated loads. A total of 5 half scale slabs (1650 × 1650 × 120 mm), subjected simultaneously to different levels of in‐plane tensile forces and a concentrated load were tested up to failure. The clear shear span to effective depth ratio a v / d was equal to 3 in all tests, to minimize the effects of the direct transmission of the load to the closest support, the so called arching action. As observed, the shear strength barely decreases with increasing values of the tensile force applied, even for values of the external force that cracked the concrete cross‐section of the slabs in the direction perpendicular to the span. These observations may indicate that the shear–flexural behavior in the spanning direction is not significantly affected by the membrane forces in the transverse direction.